(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The seeds of watermelon (Citrullus lanatus) are frequently thrown as the fruit is consumed. The seeds of three (3) types of watermelon (Charleston grey, Crimson sweet, and Black diamond) were tested for proximate, minerals, phytochemicals, total phenols content, and antioxidant activity in this study. Standard techniques were used for proximate analysis and phytochemical screening, whereas atomic absorption spectrophotometry was used to assess mineral content. The antioxidant activity and total phenol content were determined using the DPPH free radical scavenging activity and Folin-ciocalteau tests, respectively. The watermelon seeds had a moisture content of 7.40 - 8.50%, a fat content of 26.50 - 27.83%, a protein content of 16.33 - 17.75%, a fibre content of 39.09 - 43.28%, an ash content of 2.00 - 3.00%, a carbohydrate content of 9.55 - 15.32%, and an energy value of 354.05 - 369.11kcal/100g. The seeds also have significant mineral content (Ca, P, Mg, Na, K, and Zn), with K (3.40-3.5 mg/100g) being the greatest and Na (0.07 - 0.08 mg/100g) being the lowest. DPPH% inhibition ranged from 59.88 to 94.46% with trolox equivalents ranging from 82.59 to 130.29 M/g depending on the type. All samples contained saponins, tannins, triterpenoids, glycosides, and alkaloids. The total phenol content of crimson sweet seeds was the greatest (5416 mg GAE/100g), followed by Black diamond (3949 mg GAE/100g) and Charleston grey (1494 mg GAE/100g). Similarly, Crimson sweet exhibited the highest antioxidant activity, followed by Black diamond, and Charleston grey, in that order. The current findings point to watermelon seeds as a significant source of nutrients in the diet, as well as potential health and economic advantages due to their fibre, minerals, phenolic content, and antioxidant activity.